Pengujian Black Box pada Aplikasi Admin PT. World Trans Berbasis Web Menggunakan Metode Equivalence Partitioning - Adi Surya Anggana; Abyghail Shiddiq; Andrey Agung Samui; Choirul Kodri; Fahmi Ramadhan; Aries Saifudin (Teknik Informatika Universitas Pamulang, 2020)
Admin Application PT. World Trans which is being developed, found a problem in the database system that failed to communicate with the application system, namely when the admin enters the application using a user name and password, the database does not respond to data calls that are being made and the admin cannot enter the application. The development team has made improvements, and this time the test was carried out in an effort to see the possibility of the same defects or new defects in the application. So, if not tested, it will be very detrimental for business owners and other users. This test uses the Black Box testing technique. Black Box testing method consists of several ways, including Equivalence Partitioning, Boundary Value Analysis, Comparison Testing, Sample Testing, Robustness Testing, and others. Among the many testing methodologies, this test method was chosen using Equivalence Partitioning. Because Equivalence Partitioning is a Black Box testing method that breaks or divides the input domains of the program into data classes so that a test case can be obtained. The design of the Equivalence Partitioning test case is based on evaluating the equivalence class for input conditions that describe a set of conditions that are true or not. The results of this test are the admin application system PT. World Trans can make data calls to the database and there are no problems as before or new problems so that the system can run properly and according to software requirements that have been determined. With the results of this test, the development team can find out the extent of the problem in this application, as well as see the possibility of similar or new problems that can harm the team and business owners.